Eisenmenger Syndrome With Unrepaired Patent Ductus Arteriosus. Issue 16 (21st April 2015) - Ryan, John J.; Suksaranjit, Promporn; Hatton, Nathan; Bull, David A.; Wilson, Brent D.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.